2023
DOI: 10.1002/adts.202200892
|View full text |Cite
|
Sign up to set email alerts
|

Computing the Lattice Thermal Conductivity of Small‐Molecule Organic Semiconductors: A Systematic Comparison of Molecular Dynamics Based Methods

Abstract: While the Green‐Kubo and non‐equilibrium molecular dynamics methods have been compared quite extensively to calculate the thermal conductivity in inorganic compounds, there is currently a lack of comparison of these algorithms with the more recently developed approach‐to‐equilibrium molecular dynamics (AEMD) method for other types of materials such as organic semiconductors. To fill this gap, this article reports a theoretical description of thermal transport in single crystals made of terthiophene as prototyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Phonon properties of the entire 1st Brillouin zone, however, play a major role for quantities like the thermodynamic stability, the heat capacity, and all transport properties. Phonons (from within the entire 1st Brillouin zone) are the main carriers of heat in molecular crystals , and, therefore, dictate the thermal conductivities of OSCs, which typically differ between directions within and perpendicular to the planes in which the OSC molecules are arranged. Additionally, in OSCs, the coupling between charge carriers and phonons is particularly strong, thus significantly inhibiting charge carrier transport, where in recent studies, the dominant role of specific phonon modes has been identified. In the context of charge transport, it has also been shown that a proper description of electron–phonon couplings in OSCs requires the consideration of phonons from the entire 1st Brillouin zone . Measuring the phonon band structures of molecular crystals is, however, quite challenging, as it typically requires large single crystals of fully deuterated materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phonon properties of the entire 1st Brillouin zone, however, play a major role for quantities like the thermodynamic stability, the heat capacity, and all transport properties. Phonons (from within the entire 1st Brillouin zone) are the main carriers of heat in molecular crystals , and, therefore, dictate the thermal conductivities of OSCs, which typically differ between directions within and perpendicular to the planes in which the OSC molecules are arranged. Additionally, in OSCs, the coupling between charge carriers and phonons is particularly strong, thus significantly inhibiting charge carrier transport, where in recent studies, the dominant role of specific phonon modes has been identified. In the context of charge transport, it has also been shown that a proper description of electron–phonon couplings in OSCs requires the consideration of phonons from the entire 1st Brillouin zone . Measuring the phonon band structures of molecular crystals is, however, quite challenging, as it typically requires large single crystals of fully deuterated materials .…”
Section: Introductionmentioning
confidence: 99%
“…Phonons (from within the entire 1st Brillouin zone) are the main carriers of heat in molecular crystals 16 , 17 and, therefore, dictate the thermal conductivities of OSCs, which typically differ between directions within and perpendicular to the planes in which the OSC molecules are arranged. 18 21 Additionally, in OSCs, the coupling between charge carriers and phonons is particularly strong, thus significantly inhibiting charge carrier transport, 22 24 where in recent studies, the dominant role of specific phonon modes has been identified. 25 28 In the context of charge transport, it has also been shown that a proper description of electron–phonon couplings in OSCs requires the consideration of phonons from the entire 1st Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%